2015
DOI: 10.1103/physrevb.91.094507
|View full text |Cite
|
Sign up to set email alerts
|

Nontopological nature of the edge current in a chiralp-wave superconductor

Abstract: The edges of time reversal symmetry breaking topological superconductors support chiral Majorana bound states as well as spontaneous charge currents. The Majorana modes are a robust, topological property, but the charge currents are non-topological-and therefore sensitive to microscopic details-even if we neglect Meissner screening. We give insight into the non-topological nature of edge currents in chiral p-wave superconductors using a variety of theoretical techniques, including lattice Bogoliubov-de Gennes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
100
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(105 citation statements)
references
References 38 publications
5
100
0
Order By: Relevance
“…These current, however, are not a direct feature of topology, in the sense that their magnitude depends strongly on the band structure and the orientation and quality of the surface [15,24,25]. It has been shown that surface currents are essentially insensitive to changes of Chern number, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These current, however, are not a direct feature of topology, in the sense that their magnitude depends strongly on the band structure and the orientation and quality of the surface [15,24,25]. It has been shown that surface currents are essentially insensitive to changes of Chern number, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For the bulk state of SRO in the zero-magnetic field, multiple studies [1][2][3][4] , in particular, the observation of the polar Kerr effect 13 and intrinsic magnetism in µSR experiments 14 , count as evidence for the realization of a time-reversal symmetry breaking (TRSB) chiral p-wave state [1][2][3][4] . On the other hand, several experimental attempts to observe spontaneous edge currents expected for the chiral p-wave state led to negative results [15][16][17] and have triggered several theoretical studies exploring potential reasons for this conflicting result [18][19][20] . Microscopic calculations concerning the pairing symmetry show a close competition between a chiral and helical p-wave state, the former having inplane-and the latter c-axis equal-spin pairing 21 .…”
mentioning
confidence: 99%
“…II C for a complementary explanation based on the order parameter variations). By contrast, since there is no apparent spectral flow, the current in the [++] model hardly varies at finite mixing 15 . What is most striking is the inverted current flow in the [+−] model in the presence of noticeable interband mixing, given that our model employs rather moderate edge disorder (manifest in the fact that the extension of interband mixing is much narrower than the coherence length and that the ∆ y -components survive at the edge in Fig.2).…”
Section: A Bdg Resultsmentioning
confidence: 99%
“…What is most striking is the inverted current flow in the [+−] model in the presence of noticeable interband mixing, given that our model employs rather moderate edge disorder (manifest in the fact that the extension of interband mixing is much narrower than the coherence length and that the ∆ y -components survive at the edge in Fig.2). Previous one-band studies showed that current inversion is possible by varying the gap structure 15 and edge orientation in lattice models 19 . Our study therefore demonstrates an additional mechanism, interband interference, for FIG.…”
Section: A Bdg Resultsmentioning
confidence: 99%
See 1 more Smart Citation